Sec61 complex/translocon: The role of an atypical ER Ca2+-leak channel in health and disease - Parys, Jan B.; Van Coppenolle, Fabien (Frontiers in Physiology, 2022)
The heterotrimeric Sec61 protein complex forms the functional core of the so-called translocon that forms an aqueous channel in the endoplasmic reticulum (ER). The primary role of the Sec61 complex is to allow protein import in the ER during translation. Surprisingly, a completely different function in intracellular Ca2+ homeostasis has emerged for the Sec61 complex, and the latter is now accepted as one of the major Ca2+-leak pathways of the ER. In this review, we first discuss the structure of the Sec61 complex and focus on the pharmacology and regulation of the Sec61 complex as a Ca2+-leak channel. Subsequently, we will pay particular attention to pathologies that are linked to Sec61 mutations, such as plasma cell deficiency and congenital neutropenia. Finally, we will explore the relevance of the Sec61 complex as a Ca2+-leak channel in various pathophysiological (ER stress, apoptosis, ischemia-reperfusion) and pathological (type 2 diabetes, cancer) settings.